Morphometric correlations and body mass regressions for Armandia maculata, Aglaophamus macroura (Polychaeta), and Zethalia zelandica (Gastropoda) - Brian Paavo; Agnès Ziegelmeyer; Erika Lavric; P. Keith Probert (New Zealand Journal of Marine and Freshwater Research, 2008)
Armandia maculata and Aglaophamus macroura (Polychaeta) and Zethalia zelandica (Gastropoda) are abundant and conspicuous members of sandy sediment macrofaunal assemblages near dredge spoil disposal areas in southeast New Zealand. Regressions derived from data obtained by image analysis of preserved A . macroura specimens revealed that several dorsal width and area parameters of anterior chaetigers were related to total length (TL), estimated fresh weight (eFW), and ash‐free dry weight (AFDW). Length measurements were less reliable. These findings allow the development of processing protocols which use fragmented material. Total area (regardless of orientation) was related to AFDW in Ar. maculata which rarely fragment in collections. Maximum shell width was an efficient predictor of AFDW for Z. zelandica . If chosen as indicator species, these regressions allow partial automation and rapid processing of material for disposal impact studies using biomass and demographic approaches.